Promosi Dan Prevensi Penyakit Gigi Dan Mulut Masyarakat Di Desa Bandilan Kabupaten Bondowoso - Dyah Indartin Setyowati; Masniari Novita; Sri Hernawati (Dental Agromedis, 2023)
Bandilan Village is one of the underdeveloped villages in Bondowoso Regency. This village has always been a special concern of the district and provincial governments. As a fostered village of the University of Jember, one of the efforts to increase knowledge and oral health needs to be community service activities in the form of counseling and dental and oral health services. This activity can provide and overcome dental and oral health problems in the local community, especially those who have dental and oral disease problems that are delayed for treatment due to the Covid-19 pandemic situation. The method used in carrying out this community service activity is in the form of counseling and education on how to perform and maintain oral hygiene, followed by services in the form of treatment for dental and oral diseases. The results of this activity are being able to improve skills in maintaining cleanliness and oral health independently, especially in children from an early age. Meanwhile, simple dental and oral disease services can overcome dental and oral health problems that are complained by the surrounding community so that they do not continue to become complex dental and oral health problems.Keywords: Bandilan Bondowoso, Counseling, Services, Dental, Oral and health.